Effect of fermentation on structural properties and antioxidant activity of wheat gluten by Bacillus subtilis - Zhao, Peng-hui; Hou, Yin-Chen; Wang, Zhen; Liao, Ai-Mei; Pan, Long; Zhang, Jie; Dong, Yu-Qi; Hu, Zhe-Yuan; Huang, Ji-Hong; Ou, Xing-Qi (Frontiers in Nutrition, 2023)
Bacillus subtilis has been extensively studied for its ability to inhibit the growth of harmful microorganisms and its high protease activity. In this study, Bacillus subtilis was used to ferment gluten and assess the effects of the fermentation process on the physicochemical, microstructure and antioxidant properties of gluten. The results of Fourier infrared spectroscopy (FT-IR) and circular chromatography (CD) showed a significant decrease in the content of α-helix structures and a significant increase in the content of β-sheet structures in gluten after fermentation (P < 0.05). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that glutenin was degraded into small molecular peptides with a molecular weight of less than 26 kDa after 24 h of fermentation; meanwhile, the fermentation process significantly increased the free amino acid content of the samples (P < 0.05), reaching 1923.38 µg/ml at 120 h of fermentation, which was 39.46 times higher than that at 24 h of fermentation (P < 0.05). In addition, the fermented back gluten has higher free radical scavenging activity and iron reduction capacity. Therefore, fermented gluten may be used as a functional food to alleviate oxidative stress. This study provides a reference for the high-value application of gluten.